Self-expanding segmental radioactive metal stents for palliation of malignant esophageal strictures. (July 2020) - Bi, Yonghua; Li, Jindong; Yi, Mengfei; Yu, Zepeng; Han, Xinwei; Ren, Jianzhuang
Background: Traditional metal stents are not always suitable for patients with circuitous malignant esophageal stricture. Purpose: We aimed to report the safety and effectiveness of stent insertion using self-expanding segmental radioactive metal stent in the palliation of malignant esophageal stricture. Material and Methods: We conducted a retrospective analysis of 22 consecutive patients who underwent insertion of segmental radioactive metal stents from November 2016 to March 2019. Technical success, dysphagia score, and complications were analyzed. Kaplan–Meier analysis was used to analyze the survival time. Results: The stenting procedure was successful in all 22 patients with no procedure-related deaths. Twenty-four segmental radioactive metal stents were successfully implanted. A total of 6 (27.3%) complications were found, mainly 5 (22.7%) stent migrations. The median follow-up period was 3.3 months. Stent removal was required in 4 (12.5%) patients due to complete stent migration. The mean dysphagia score decreased significantly after stent insertion ( P <0.0001). During follow up, 13 patients survived with no obvious clinical symptom and nine patients died. The mean survival was 9.9 months. Conclusion: The stenting procedure using self-expanding segmental radioactive metal stents is safe and effective in dysphagia palliation of malignant esophageal stricture.